2020
DOI: 10.1242/dev.193623
|View full text |Cite
|
Sign up to set email alerts
|

Plant homeodomain proteins provide a mechanism for how leaves grow wide

Abstract: The mechanisms whereby leaf anlagen undergo proliferative growth and expansion to form wide, flat leaves are unclear. The maize gene NARROWSHEATH1 (NS1) is a WUSCHEL-related homeobox3 (WOX3) homolog expressed at the margins of leaf primordia, and is required for mediolateral outgrowth. To investigate the mechanisms of NS1 function, we used chromatin immunoprecipitation and laser-microdissection RNAseq of leaf primordial margins to identify gene targets bound and modulated by NS1. Microscopic analyses of cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…These hormones also modulate PD growth and leaf length by controlling the size of the division zone during steady‐state growth (Nelissen et al ., 2012; De Vos et al ., 2020). Auxin, on the contrary, is involved in ML patterning via the regulation of adaxial–abaxial polarity by small regulatory RNAs (Douglas et al ., 2010; Dotto et al ., 2014), delineation of the margins (Johnston et al ., 2015), and promotion of marginal outgrowth by duplicate WOX3 ( WUSCHEL‐RELATED HOMEOBOX3 ) genes NARROWSHEATH1/2 ( NS1/2 ), which are the maize co‐orthologs of PRESSED FLOWER ( PRS ) in Arabidopsis (Matsumoto & Okada, 2001; Nardmann et al ., 2004; Conklin et al ., 2020). While these studies have discovered links between auxin, CK, and GA in axial patterning, a comprehensive understanding of how these plant hormones control ML growth and vein formation remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…These hormones also modulate PD growth and leaf length by controlling the size of the division zone during steady‐state growth (Nelissen et al ., 2012; De Vos et al ., 2020). Auxin, on the contrary, is involved in ML patterning via the regulation of adaxial–abaxial polarity by small regulatory RNAs (Douglas et al ., 2010; Dotto et al ., 2014), delineation of the margins (Johnston et al ., 2015), and promotion of marginal outgrowth by duplicate WOX3 ( WUSCHEL‐RELATED HOMEOBOX3 ) genes NARROWSHEATH1/2 ( NS1/2 ), which are the maize co‐orthologs of PRESSED FLOWER ( PRS ) in Arabidopsis (Matsumoto & Okada, 2001; Nardmann et al ., 2004; Conklin et al ., 2020). While these studies have discovered links between auxin, CK, and GA in axial patterning, a comprehensive understanding of how these plant hormones control ML growth and vein formation remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of tube-shaped leaves in maize can be induced by incubation with the auxin inhibitor NPA (Scanlon, 2003) which leads to a failure of sheath margin separation, and this correlates with a high accumulation of ZmPIN1a in this region at the P4 stage of leaf development (Johnston et al, 2015). Recent work has also shown that NS1 is induced by auxin treatment (Conklin et al, 2021). This suggests that ZmIAA28 may be involved in translation of the auxin concentration signal to leaf margin specification and later margin development.…”
Section: Discussionmentioning
confidence: 99%
“…Mediolateral development in the leaf is driven by WOX gene activity (Conklin et al, 2021; Zhang et al, 2020). Our transcriptional analyses highlight wide-spread miss-regulation of WOX gene expression in Oja , with most significant downregulation associated with potential tube leaf formation, and failure of leaf initiation.…”
Section: Discussionmentioning
confidence: 99%
“…A close examination of Streptochaeta may provide insight into how leaf angle is controlled in diverse grasses. Leaf width in maize is controlled particularly by the WOX3 -like homeodomain proteins NARROWSHEATH1 ( NS1 ) and NS2 , which function in cells at the margins of leaves ( Scanlon et al, 1996 ; Conklin et al, 2020 ). Duplication patterns and expression of NS1 and NS2 genes in the Streptochaeta genome could test whether the models developed for maize were present in the earliest of grasses.…”
Section: Discussionmentioning
confidence: 99%